Exposing the problem of air pollution in India - a study - Vamsi, Varahabhatla (Запорізький державний медичний університет, 2017)
Relevance. Outdoor air pollution is a major environmental health problem affecting everyone in developed and developing countries alike. WHO estimates that in 2012; 72% of outdoor air pollution-related premature deaths were due to ischaemic heart disease and strokes, whereas 14% of the deaths were due to chronic obstructive pulmonary disease or acute lower respiratory infections and 14% of them were due to lung cancer [WHO, 2016]. Every year, roughly 5.8 million Indians die from heart and lung diseases, stroke, cancer and diabetes. In other words, 1 in 4 Indians risks dying from an NCD before they reach the age of 70 [WHO, 2015].
Keywords: тези